2006
DOI: 10.1111/j.1532-950x.2006.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of Two Loop Tensioning Methods for Crimp Clamp Extracapsular Stabilization of the Cranial Cruciate Ligament‐Deficient Canine Stifle

Abstract: The hand tightening method described is a valuable technique for unassisted surgeons without access to tensioning devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…The larger distribution of data points for the CC has been attributed to human error in grip strength when crimping, and could represent inconsistency in technique in live patients in inexperienced hands . Banwell et al reported static testing of nonmedical grade 40# nylon secured with Securos® CC with quite high variance (29%) in their results and slippage through the clamp compared to 60# and 80# nonmedical grade nylon constructs .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The larger distribution of data points for the CC has been attributed to human error in grip strength when crimping, and could represent inconsistency in technique in live patients in inexperienced hands . Banwell et al reported static testing of nonmedical grade 40# nylon secured with Securos® CC with quite high variance (29%) in their results and slippage through the clamp compared to 60# and 80# nonmedical grade nylon constructs .…”
Section: Discussionmentioning
confidence: 99%
“…Lateral ECS transiently controls hyperextension, cranial drawer motion, and internal rotation of the tibia while periarticular fibrosis progresses . Mechanical properties of materials used for ECS including ultimate tensile strength, stiffness, and elongation have been compared in vitro . Ideally, ECS would be performed using a strong, relatively stiff material that has minimal elongation and a secure knotting method that is not bulky, yet is simple to perform with minimal instrumentation or assistance …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Jig construction was similar to previous studies. 21,30 Crimps were clamped using a compound-action crimper (Veterinary Instrumentation) as described by Moores et al 34 Briefly, partial clamping of the crimp was followed by progressive loop tightening before definitive clamping. Initial partial clamping was in the middle of the crimp and final clamping in 3 evenly spaced locations of the crimp and away from the end of the crimp.…”
Section: Specimensmentioning
confidence: 99%